Systematic Literature Review: Patterns, Factors, and Managerial Implications on Muzakki Loyalty - Abi Suar; Zandy Pratama Z; Syahrial Maulana; Hijrasil Hijrasil; Alda Sri Lupita; Saipul Azis (Mauriduna : Journal of Islamic Studies, 2025)
This study aims to investigate Patterns, Factors, and Managerial Implications on Muzakki Loyalty to identify what research is needed in the future. In addition, it also explores the relationship model between how the current Muzakki Loyalty publication trend is and how the results of the systematic literature review are the direction of future research. The design/methodology/approach in this study uses a systematic literature review and Meta-Analyses (PRISMA) analysis by reviewing articles published in 2014 to 2023. The PRISMA procedure involves several stages, including identification, screening, eligibility, analysis and conclusions based on the findings. The results of the study found that muzakki loyalty to zakat institutions is greatly influenced by various key factors, including transparency, accountability, service quality, customer relationship management (CRM), institutional image, and religiosity values. Transparency and accountability in the management of zakat funds provide trust to muzakki, ensuring that the funds they donate are managed in a trustworthy manner and in accordance with sharia principles. Responsive and professional service quality increases muzakki satisfaction, making them more emotionally attached to zakat institutions. In addition, the implementation of CRM and the positive image of the institution, as seen in BAZNAS and Lazizmu, creates a deeper personal relationship with muzakki, increasing their trust and commitment. Religious values also strengthen loyalty, especially when zakat institutions demonstrate compliance with Islamic principles in governance and services. By integrating these elements, zakat institutions can build long-term loyalty from muzakki, ensuring continued support in the management and distribution of zakat.